How Our Caregivers Shape Who We Are: The Seven Dimensions of Attachment at the Core of Personality - Gagliardi, Marcantonio (Frontiers in Psychology, 2021)
Psychology defines personality as the stable traits of an individual, and cognitive research suggests that a set of core beliefs is at the root of these traits. From this perspective, two major questions remain unanswered: (1) What are the core beliefs that make up personality? (2) How are they acquired? An interesting answer is provided by attachment theory, according to which attachment is at the basis of personality. The current theoretical formulation, however, does not sufficiently clarify the relationship between the two. Adopting a cognitive-clinical approach, we put forward a novel version of attachment theory, arguing that it can better account for the relationship between attachment and personality, thereby providing more convincing answers to questions (1) and (2). In particular, we propose that: (A) attachment information is acquired over seven dimensions; (B) the acquisition of each dimension is induced by a specific caregiving feature and (C) realized through a specific acquisition mechanism – imprinting. In a nutshell, we propose an Attachment-Personality Model (APM) according to which seven attachment dimensions constitute the knowledge core of personality. We finally discuss the significant implications of the model, especially its clinical application in terms of conception, assessment, and treatment of mental disorders. The model can be empirically tested, and we suggest three ways to do that.